Self-Harm and Suicidal Behaviors in Hong Kong Adolescents: Prevalence and Psychosocial Correlates - Daniel T. L. Shek; Lu Yu (The Scientific World Journal)
The present paper examined the prevalence and psychosocial correlates of adolescent deliberate self-harm (DSH) and suicidal behavior in a representative sample of 3,328 secondary school students in Hong Kong. With reference to the previous year, 32.7% of the students reported at least one form of DSH, 13.7% of the respondents had suicide thoughts, 4.9% devised specific suicidal plans, and 4.7% had actually attempted suicide. Adolescent girls had significantly higher rates of DSH and suicidal behavior than did adolescent boys. Having remarried parents was related to an increased likelihood of DSH and suicide. While high levels of family functioning, overall positive youth development, and academic and school performance predicted low rates of DSH and suicidal behavior, cognitive and behavioral competencies were unexpectedly found to be positively associated with DSH and suicidal behavior. Theoretical and practical implications of the findings are discussed.